Chirality Transfer, Memory and Sensing Activated by a Supramolecular Chiral Auxiliary Approach in Nanostructured, Tautomerically Prochiral Triptycene-Fused Benzimidazoles - Giovanni Preda; Riccardo Mobili; Giovanna Longhi; Massimiliano Meli; Giorgio Colombo; Valeria Amendola; Dario Pasini (Journal of the American Chemical Society, 2026)
Abstract We report the synthesis and characterization of stimuli responsive, adaptive organic chiral nanoparticles assembled using a “stereochemically fluid”, triptycene-fused benzimidazole, which is chiroptically activated by the noncovalent interaction with enantiopure tartaric acid, acting as a “supramolecular chiral auxiliary”. Under appropriate experimental conditions, the formation of chiral supramolecular aggregates exhibits remarkable chiroptical properties (electronic circular dichroism, ECD, and circularly polarized luminescence, CPL) with the possibility of addressing their controlled manipulation, reversion between the states, and chirality memory properties. Furthermore, the nanostructured system is capable of selective sensing of the Cu2+ ion through the modulation of its chiroptical properties. In this manner, we provide an unprecedented way to introduce chirality onto the triptycene skeleton to assemble well-defined chiral nanoparticles with dimensions of several hundred nanometers and to reversibly store chiral information and activate chiroptical sensing properties.